COMPARATIVE STUDY BETWEEN SRTM IMAGES AND ARMY LETTERS TO THE STUDY OF ALTIMETRIC PLAN IN WATERSHED - Löbler, Carlos Alberto; Ssccoti, Anderson Augusto Volpato; Terra, Lueni Gonçalves; Ertel, Tiago; Silva, José Luiz Silvério da (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
The mapping of the Brazilian territory does not have full coverage. One way to solve this gap is through the use of satellite images. One of these products are the images SRTM (Shuttle Radar Topography Mission), which have very important information for environmental studies. Yet still lacks theoretical foundation regarding the reliability of this basemap. Thus, this study aims to compare the information on SRTM altimetry in the images with the information contained in topographic maps made by the brazilian army in the 70s. Was studied the watershed Arroio do Veado located between the cities of Santa Maria and Silveira Martins, in the transition zone between Central Depression and Serra Geral Plateau, in the Rio Grande do Sul state, southern Brazil. Using the ArcGIS software were extracted contour lines that served as bases and then generated the digital terrain model and slope map of the basin. It was observed that the data resulting from the two cartographic databases are very similar using a map scale 1: 50 000 applied to watersheds with one area circa the 4,000 hectares. Was concluded, with these conditions may be used SRTM images, useful, handling and wide coverage in Brazil.